AKTIVITAS BELAJAR SISWA DALAM METODE PROBLEM SOLVING PADA MATA PELAJARAN IPS DI SMP 2 KESESI KABUPATEN PEKALONGAN - Pratama, Bregas Widya (Jurnal Geografi, 2016)
This research aims to understand the level of student learning activity in the method of problem and understandmethod problem solving learning of teacher on the subjects of social class in Junior High School 2 KesesiPekalongan District . Data collection technique that is used is a method of observation .Data analysis techniqueof the research is descriptive statistics with using analysis the frequency . The results showed that (1) the activityof the students on the methods of problem solving are included in the criteria they have actively covering theactivities realized the problem, formulating problems, formulate a hypothesis, collect data, and test thehypothesis. Whereas, in the activity of drawing up and presenting the report categorized quite active, becausethere are only few people who completed the report and actively speak, the language is still in the mix, as well asthe courage of the student when asked the answer still looks hesitant. (2) Learning use the method problemsolving implemented teacher in the category of good because teacher have carry out three stages, namelypreparation, the implementation, and evaluation. But the teacher is weak creative in media uses learning. Toimprove student learning activity is expected to read more books , looking for trouble from various sources ,practice speaking in front of class , discussions , asked responsibility , and exchanging ideas. For teacher shouldgreater use of media learning such as making power point slide and mind mapping.